IFPA meeting 2015 workshop report IV: placenta and obesity; stem cells of the feto-maternal interface; placental immunobiology and infection. (December 2016) - Abumaree, M.H.; Almutairi, A.; Cash, S.; Boeuf, P.; Chamley, L.W.; Gamage, T.; James, J.L.; Kalionis, B.; Khong, T.Y.; Kolahi, K.S.; Lim, R.; Liong, S.; et al.
Abstract: Workshops are an important part of the IFPA annual meeting as they allow for discussion of specialised topics. At the 2015 IFPA annual meeting there were 12 themed workshops, three of which are summarized in this report. These workshops related to various aspects of placental biology and collectively covered areas of obesity and the placenta, stem cells of the feto-maternal interface, and placental immunobiology and infection.